Review of Trust-based Security Models forPacket Routing in Wireless Sensor Networks - Dinesh Kumar, Vikram Singh, Sangeeta Rani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In wireless sensor networks, routing deals with the delivery of data from a sensor node to the base station. Any attack on the routing mechanism can degrade or paralyze the operations of a wireless sensor network. Authentication and cryptographic solutions to thwart such attacks do not work, for these mechanisms are implemented using compromised nodes. Of lately, several trust-based schemes have been proposed to augment the security by excluding or including nodes in a route depending upon their computed trust values. Different trust mechanisms have been proposed to deal with different kinds of routing attacks. The present article reviews the current state of research in trust-based protocols for thwarting routing attacks in wireless sensor networks.